PI controller for battery charger system - Mohd Azhar, Azmi (2008)
There are many type of battery charger that had been developed for century. However there are also many charger that not suitable to use due to the method of charging and the safety during the charging process. Normally the charger will automatically charge the battery pack when it is connected to the charger, but it keeps charging even though the battery is fully charged. This situation can damage the battery itself or the user if explosion occur during the process. Beside that, the lifetime of the battery is also important. A good charging method can increase the lifetime of the battery. PI controller can control the output voltage from the charger to meet a desire value by controlling the rise time of the current, overshoot and error that occur during charging process. The Proportional (P) action will decrease the rise time and decrease error while Integral (I) action will eliminate the error occur. This project is developed to investigate the action of PI controller to the output from battery charger.